THE RELATIONSHIP BETWEEN SLEEP QUALITY AND BLOOD PRESSURE IN ELDERLY WOMEN WITH HYPERTENSION - Tiyaswati, Yeni Candra; Ekasari, Mia Fatma; Maryam, Raden Siti; Badriah, Siti; Lestari, Puspita Hanggit (Jurnal Keperawatan, 2025)
The elderly population is particularly vulnerable to various health issues, including sleep disturbances and hypertension. Poor sleep quality can lead to increased blood pressure by stimulating the sympathetic nervous system and elevating stress hormones. This study explored the relationship between sleep quality and blood pressure among elderly women with hypertension. This study uses a quantitative method with an analytical descriptive design with a cross-sectional approach. The sampling technique in this study used purposive sampling with a sample of 67 elderly women with hypertension. The instruments used were the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality and a digital sphygmomanometer to measure blood pressure. The data analysis in this study used the Chi-Square test. Most of the elderly had poor sleep quality as many as 50 elderly (74.6%) and degree II hypertension as many as 44 elderly people (65.7%). The results of statistical tests showed a significant relationship between sleep quality and blood pressure in elderly women with hypertension, as evidenced by obtaining a p-value of 0.000 (<0.05).Poor sleep quality in people with hypertension can lead to memory impairment, cognitive abilities, and decreased health. It is hoped that the role of the family and the community health center will be to carry out monitoring and evaluation and motivate the elderly to control blood pressure and sleep regularly.